Apparent diffusion coefficient ratio between axillary lymph node with primary tumor to detect nodal metastasis in breast cancer patients. Issue 4 (25th February 2013) - Luo, Ningbin; Su, Danke; Jin, Guanqiao; Liu, Lidong; Zhu, Xuna; Xie, Dong; Liu, Younan
Abstract : Purpose: To evaluate the ratios of apparent diffusion coefficient (ADC) calculated from diffusion weighted imaging (DWI) between axillary lymph nodes with primary breast tumor lesions in the detection of axillary lymph nodes metastasis in breast cancer patients. Materials and Methods: A total of 36 patients with breast tumors and their axillary lymph nodes were included in this study for MR image scan. The ADC values were calculated using DW‐MR imaging software. The ADC values and the ADC ratios of axillary lymph nodes in patients with primary breast lesion were compared among benign and metastatic axillary lymph nodes. All the diagnosis were confirmed by histopathological examination. Results: The mean ADC value of metastatic lymph nodes was significantly lower than those of benign lymph nodes (0.787 × 10 −3 mm 2 /s ± 0.145 versus 1.043 × 10 −3 mm 2 /s ± 0.257) ( P < 0.05). In addition, ADC ratio of metastatic lymph nodes with breast lesion was significantly lower than those of benign lymph nodes with breast tumor lesions (0.986 ± 0.17 versus 1.375 ± 0.417) ( P < 0.05). Once the ADC ratio was fixed at 0.889 × 10 −3 mm 2 /s, the sensitivity, specificity, and accuracy were 82.22%, 82.35% and 82.28%, respectively. The cutoff of ADC ratio was at 1.097 × 10 −3 mm 2 /s, the sensitivity, specificity, and accuracy can be up to 84.44%, 88.24%, and 86.08%. Conclusion: ADC value and ADC ratio could be used as a reliable parameter to detect the axillary lymph nodes metastasis in breast cancer patients, and ADC ratio has a higher accuracy. J. Magn. Reson. Imaging 2013;38:824–828. © 2013 Wiley Periodicals, Inc.